The double-edged effects of screen time and time management practices on the academic performance of Cambodian accountancy students - Cadungog-Uy, Juliet; Flores, Edman P (Journal of Education and e-Learning Research, 2025)
The study examines the impact of screen time and time management practices on the academic performance of Cambodian accountancy students. A quantitative approach was adopted using a structured questionnaire administered to 663 students. The research explores educational and non-educational screen time usage, perceived benefits, and time management strategies. Data analysis involved descriptive statistics, chi-square tests, and one-way ANOVA. The findings indicate a positive relationship between educational screen time and academic performance as measured by CGPA. Students recognize the advantages of educational screen time in enhancing digital literacy and facilitating self-paced learning. Surprisingly, the results also show a positive relationship between non-educational screen time and CGPA. Additionally, no significant relationship was found between time management practices and CGPA. These outcomes challenge conventional assumptions, suggesting that other factors, such as the ability to regulate screen time and manage distractions may play a crucial role in academic success. The study underscores the importance of promoting balanced digital habits and effective self-regulation strategies. Ultimately, this research serves as a valuable resource for teachers and policymakers, offering insights to enhance student performance and well-being in the digital era. By fostering a more supportive learning environment for Cambodian accountancy students, it provides a foundation for future studies to explore causal relationships and the specific content of screen time usage to refine these conclusions further.